The implementation of AutoCAD® Civil 3D for highway geometric redesign: a case of Indonesian toll road - Rifai, A I; Purviyanto, E J; Prasetijo, J (2023)
Transportation infrastructure is one of the primary needs in increasing a country's economic growth. In the last decade, Indonesia has continued to build toll roads to accelerate the provision of these needs. In some toll road development projects, a redesign is required as a form of field adaptation. The redesign process requires accuracy, speed, and convenience, so the development process goes according to plan. This paper discusses the implementation of using AutoCAD® Civil 3D for toll road redesign in Indonesia. The data is taken from the construction of toll roads in the Greater Jakarta-Indonesia area in 2023. The research method was carried out by comparing manual calculations and AutoCAD® Civil 3D. The study results show that some adjustments to the toll road design must be implemented faster and more precisely according to field needs. The selection of these applications makes it easier for designers to determine various options for planning the toll road. The conclusion of this paper shows that the use of AutoCAD® Civil 3D increases the efficiency and effectiveness of toll road redesign